Розвиток регіонального підприємництва з використанням світового досвіду в умовах воєнного конфлікту - Бессонова, С. І.; Бессонова, С. И.; Bessonova, S. (ЦНТУ, 2019)
У статті досліджено сучасний стан регіонального підприємництва та висвітлено проблемні аспекти внутрішньопереміщених осіб, які виникли в умовах воєнного конфлікту. Проаналізовано роль підприємництва в європейських країнах, розкрито види економічної діяльності, в яких вітчизняне підприємництво досягло значного зростання. З’ясовані можливості створення нових робочих місць на регіональному та місцевому рівні, а також нових платформ для перепідготовки молодих підприємців, отримання знань, навичок та компетенцій для створення власного інноваційного/ інвестиційного бізнес-проекту, організації бізнесу відповідно до сучасного попиту на ринку праці або соціального бізнесу, а також створення взаємодії зі стейкхолдерами для розвитку підприємницьких можливостей. This article explores current state Regional business and highlights the problematic aspects internally displaced persons those arising in terms of military conflict. The loss of resources and assets in the occupied territories affected not only large companies but also small businesses, medium businesses and households. Therefore, the actual problem is the creation of conditions for development of small and medium business, fighting unemployment, reducing the flow of emigration of the population. Current state Regional business located in instability. Therefore, implicated a number of reasons such as the unstable economic situation, changes in legislation, leaving young people abroad, low wages and problematic aspects internally displaced persons those arising in terms of military conflict. Analysis of business in European countries adopting promotes demand for domestic entrepreneurs. Important at local and regional levels to create conditions to overcome unemployment, reduce the flow of migration from Ukraine, created jobs, especially among internally displaced persons, creating a competitive environment and develop optimal forms of interaction and cooperation of large and small businesses in the region. A negative fact considers the introduction of mandatory early next year application almost all subjects of entrepreneurial activity settlement registrar, which will have a negative impact on the activities of many businesses.
Развитие регионального предпринимательства с использованием мирового опыта в условиях военного конфликта
The Development of Regional Entrepreneurship Using World Experience in a Military Conflict
Keywords: підприємництво; діяльність суб’єктів господарювання; рівень безробіття; підприємства малого та середнього бізнесу; предпринимательство; деятельность субъектов хозяйствования; уровень безработицы; предприятия малого и среднего бизнеса; entrepreneurship; activity of economic entities; unemployment rate; small and medium-sized enterprises